1998
DOI: 10.1051/forest:19980306
|View full text |Cite
|
Sign up to set email alerts
|

Bending properties of Norway spruce timber. Comparison between fast- and slow-grown stands and influence of radial position of sawn timber

Abstract: -The primary objective of this work was to study one aspect of improving timber quality. The aim of this paper is to supplement previously published results in Wood Science and Technology. Bending strength and stiffness of Norway spruce (Picea abies) from three stands in southern Sweden, two fast-grown and one slow-grown, were measured. Radial variations were studied using six studs (45 mm x 70 mm x 2 900 mm) per log cut along a diameter, with a total of 500 studs. The bending strength of studs from the slow-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…For planted Norway spruce trees, density was found to decrease across the first three to five annual rings, and then slightly increase further throughout the mature wood (Kuçera 1994). Kliger et al (1998) found the same pattern. The longitudinal variation in density shows divergent patterns.…”
Section: Introductionsupporting
confidence: 61%
“…For planted Norway spruce trees, density was found to decrease across the first three to five annual rings, and then slightly increase further throughout the mature wood (Kuçera 1994). Kliger et al (1998) found the same pattern. The longitudinal variation in density shows divergent patterns.…”
Section: Introductionsupporting
confidence: 61%
“…The similarity of the results of the static and dynamic modulus of elasticity (MOE) is the basis for successful use of these methods in practice. Some studies show a very close dependence (with the correlation coefficient of up to 0.96) of the static and dynamic MOE (Tanaka et al 1991;Perstorper 1994;Ilic and Ozarska 1996;Kliger et al 1998;Ilic 2001), although the values of the dynamic measurements themselves are often somewhat higher than in the case of static tests (Cho 2007;Hassan et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…1. In general, sawn timber from spruce has a modulus of elasticity of around 8 to 15 GPa, a dry density of roughly 300 to 500 kg/m 3 , and a bending strength of around 30 to 60 MPa (Kliger et al 1998;Johansson and Kliger 2002;Hanhijärvi and Ranta-Maunus 2008;Raftery and Harte 2013). For pine, the material properties are rather similar, with a modulus of elasticity of around 8 to 12 GPa, a dry density of about 300 to 500 kg/m 3 , and a bending strength of 30 to 45 MPa (Hanhijärvi and Ranta-Maunus 2008).…”
Section: Methodsmentioning
confidence: 99%